1993
DOI: 10.1177/107554709301500207
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Value of Information

Abstract: Information theorists have long struggled with the problem of establishing a mechanism for the valuation of the enigmatic substance of data. With the relatively recent advent of electronic databases, on-line access, and the importance of telecommunications, this question has received growing attention. This article reviews, from the perspective of a computer scientist, commonly accepted notions of information value, before rejecting them and insisting upon the importance of using an economic commodity value ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Peter Drucker introduced the idea of a knowledge economy to business management, writing about ''knowledge workers'' as early as 1959. Drucker echoed older wisdom, including Adam Smith's observation that knowledge builds business value (Bellin 1993;Ichijo and Nonaka 2007) and GWF Hegel's premise that organizational value accrues from continually synthesizing old information with new (1837/1997). Reflection builds organizational knowledge, which is organizational value (Argyris and Schön 1978;Peake and Epstein 2004;Schön 1983;Gilbert 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Peter Drucker introduced the idea of a knowledge economy to business management, writing about ''knowledge workers'' as early as 1959. Drucker echoed older wisdom, including Adam Smith's observation that knowledge builds business value (Bellin 1993;Ichijo and Nonaka 2007) and GWF Hegel's premise that organizational value accrues from continually synthesizing old information with new (1837/1997). Reflection builds organizational knowledge, which is organizational value (Argyris and Schön 1978;Peake and Epstein 2004;Schön 1983;Gilbert 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Researchers have addressed the business value of information in extant literature across different information value domains: Hubbard and Schmarzo have addressed the economic value of information (Hubbard, 2014;Schmarzo, 2016); Arrow and Bellin have discussed valuing information as a commodity (Arrow, 2012;Bellin, 1993); and Bates, Bellin and Laney have considered information's business use (Bates, 1990;Bellin, 1993;Laney, 2012Laney, , 2018. Laney has also gone further in segregating business use into realized, probable and potential values (Laney, 2012(Laney, , 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This further evolved with the introduction of knowledge management in organizations in the 1980s and 1990s (Black and Manchand, 1982). The current phase addresses how intangible assets can be measured (Baruch, 2003;Bates, 1990;Bellin, 1993;Higson and Waltho, 2009) and how they can be understood in the manner of more traditional physical assets (Hubbard, 2014;Laney, 2018). In the past 10 years infonomics further developed and evolved methods for valuing information.…”
Section: Information Valuementioning
confidence: 99%
“…Economists have tried to model this use‐value approach but, because it excludes marketplace considerations, these analyses do not help with pricing decisions. Exchange value and use value are not necessarily the same—some information will lose exchange value through use, but the potential exchange value of other information will increase with use (Bellin, 1993). Eaton (1987) concluded that the value of information eludes precise calculation, noting that it is entirely dependent upon context, use, and outcome.…”
Section: The Pricing Of Information and Information Goodsmentioning
confidence: 99%